Barriers to transition towards sustainable mobility in Sub-Saharan African cities: The case of Maputo and Freetown - Clémence Cavoli; Daniel Oviedo; Alexandria Z.W. Chong; Yasmina Yusuf; Joseph Mustapha Macarthy; Braima Koroma; Joaquín Romero de Tejada; Constâncio Augusto Machanguana (Sustainable Futures)
This paper explores the extent to which growing cities in Sub-Saharan Africa can accelerate and leapfrog their urban development processes to avoid unsustainable car-dependent developments and instead pursue alternative sustainable mobility transitions. Taking Maputo, Mozambique, and Freetown, Sierra Leone, as case study cities, the paper aims to identify the most common structural issues underpinning transport and land-use that hinder these cities from transitioning towards sustainable and just mobility. Through 38 interviews with professional stakeholders, policymakers, and representatives of local communities, the paper identifies and examines key barriers within governance, policymaking, and planning processes to enable medium- to long-term changes in both cities. These include: (i) land-use and urban planning; (ii) governance issues in planning and policymaking; (iii) institutional and technical capacity; (iv) regulations, implementation, and enforcement; and (v) finance and revenue. The paper concludes by offering targeted policy recommendations to enhance institutional and technical capacity in transport and land-use policy, planning, implementation, and enforcement processes.